Teachers’ Implementation of CEFR-aligned Curriculum: A Preliminary Study - Chong, Gloria; Yamat, Hamidah (Journal of English Language Teaching and Applied Linguistics, 2021)
This paper acted as a preliminary study to discover the degree of Malaysian teachers’ readiness in CEFR implementation and the CEFR implementation practices in the English as the second language (ESL) classroom. This study implies a survey research design. An online google form survey questionnaire was disseminated to in-service teachers through convenient random sampling. The respondents are twenty Malaysian primary school ESL teachers from different school settings. The respondents answer a closed-ended questionnaire that elicits their readiness in the CEFR-aligned curriculum implementation and their frequency in using the CEFR-aligned curriculum’s resources and assessment. The online data gathered were tabulated and further analysed using IBM SPSS Statistics version 22. This study concludes that the CEFR-aligned curriculum is moving in a positive direction. However, the overall readiness for the implementation needs more improvements, and the resources given should be into full use.